Social Representations of LGBT Old Age and Sex Workers in Brazilian Adults - Lima Filho, Gutemberg de Sousa (2022)
Background: The number of elderly people in the world is growing significantly, so there is an urgent need to ensure that this population can live a full life, especially taking into account the current COVID-19 pandemic scenario. Objective: To analyze the social representations of LGBT old age for male and female sex workers through the pandemic. Method: A qualitative, descriptive, and exploratory research conducted with 10 male and 10 female sex workers aged between 18 and 48. Sociodemographic questionnaires and semi-structured interviews were administered using Google Forms and then analyzed by descending hierarchical classification through the IRaMuTeQ software. Results: The analysis showed three classes: (1) «Social understanding of the topic LGBT old age,» (2) «Stigma of genders and sexual orientations,» and (3) «Physical transformations and their accompanying obstacles». Conclusions: The representations are associated with the difficulties that elderly people have with aging in society, as well as debating LGBT old age. There are also greater obstacles regarding aging of female sex workers. In this way, the study seeks to contribute to broaden the knowledge of the psychosocial aspects of LGBT aging and old age, especially those of sex workers.